Comparison of the use of a braided multifilament transfixation suture for field castration with other castration techniques. (23rd September 2017) - Koenig, J. B.; Sinclair, M.; Sorge, U. S.
Summary: Complications with castrations occur commonly and are usually not life‐threatening, with the exception of evisceration or haemorrhage, which are uncommon. Primary closure castration (closing deeper tissue layers and skin) or use of a transfixation ligature alone to prevent evisceration has been recommended. The goal of this study was to investigate the use of a closed technique with multifilament suture for transfixation of the spermatic cord alone in field castrations. The results of this study support our hypothesis that a closed castration technique with a multifilament, transfixing ligature (No. 2 polyglactin 910) did not result in additional post‐operative complications when compared with a closed castration technique without ligature placement or a primary closure castration technique in a hospital setting.